PM10‐stimulated airway epithelial cells activate primary human dendritic cells independent of uric acid: Application of an in vitro model system exposing dendritic cells to airway epithelial cell‐conditioned media. Issue 6 (15th May 2014) - Hirota, Jeremy A.; Alexis, Neil E.; Pui, Mandy; Wong, SzeWing; Fung, Elkie; Hansbro, Phillip; Knight, Darryl A.; Sin, Don D.; Carlsten, Chris
Abstract Background and objective Airway epithelial cells represent the first line of defence against inhaled insults, including air pollution. Air pollution can activate innate immune signalling in airway epithelial cells leading to the production of soluble mediators that can influence downstream inflammatory cells. Our objective was to develop and validate a model of dendritic cell exposure to airway epithelial cell‐conditioned media. After establishing the model, we explored how soluble mediators released from airway epithelial cells in response to air pollution influenced the phenotype of dendritic cells. Methods Human airway epithelial cells were cultured under control and urban particulate matter (PM10) exposure conditions with or without pharmacological inhibitors of the uric acid pathway. Culture supernatants were collected for conditioned media experiments with peripheral blood mononuclear cell‐derived dendritic cells analysed by flow cytometry. Results Monocytes derived from peripheral blood mononuclear cells cultured in interleukin‐4 and granulocyte macrophage colony stimulating factor differentiated into immature dendritic cells that phenotypically differentiated into mature dendritic cells in response to conditioned media from phorbol myristate acetate‐activated THP‐1 monocytes. Exposure of immature dendritic cells to conditioned media from airway epithelial cells exposed to PM10 resulted in dendritic cell maturation that was independent of uric acid. Conclusions We present a conditioned media model useful for interrogating the contribution of soluble mediators produced by airway epithelial cells to dendritic cell phenotype and function. Furthermore, we demonstrate that PM10 exposure induces airway epithelial cell production of soluble mediators that induce maturation of dendritic cells independent of uric acid.